Spirituality and Sustainability New Horizons and Exemplary Approaches - Dhiman, Satinder; Marques, Joan (Springer International Publishing : Imprint: Springer, 2016)
This book aims to examine sustainability and spirituality philosophically with ethics as the balancing force. The goal is to reveal the important intersection between sustainability and spirituality by using spirituality as the invisible guiding hand in the quest for sustainability. The editors and contributors examine old social and economics dilemmas from a new perspective in order to provide alternative approaches to economic and social development. The enclosed contributions cover a broad range of topics such as sustainable development and human happiness, contemporary spirituality, environmental ethics and responsibility, and corporate social responsibility. In addition, the title features real-world case studies and discussion questions that inspire self-reflection and theoretical and empirical deliberation in academic courses and business seminars. Contemporary approaches to economic and social development have failed to address humankind's abiding need for spiritual growth. For material development to be sustainable, spiritual advancement must be seen as an integral part of the human development algorithm. While the policy makers and governments can play their respective role, each one of us has to consciously adopt spirituality and sustainability as a way of life. This book will rely on the spiritual power of individuals to heal themselves and the environment. Featuring interdisciplinary perspectives in areas such as science, marine biology, environmental policy, cultural studies, psychology, philosophy, ecological economics, and ethics, this book will provide extensive insights into the complimentary fields of spirituality, sustainability and ethics.